Physiological performance of RR soybean seeds in Glyphosate subdoses submitted to biostimulant (Research, Society and Development, 2020)
Transgenic soybean has a mechanism of resistance to glyphosate, but there are studies that demonstrate negative effects of this herbicide on the initial stage of seed development. There are also reports that the use of the biostimulant prevents the loss of seed vigor in the initial phase when in contact with Glyphosate. This study aimed to evaluate the effect of glyphosate and biostimulant underdoses on soybean seeds. A completely randomized design in a 2x5 factorial scheme was used, with four replications. The seeds were subjected to five sub-doses of Glyphosate zapp 620 (0; 3.5; 7.0; 10.5 and 14 mL-1 L) and seed treatment with Stimulate® at 0 and 7.5 mL L-1. In the laboratory, the experimental units consisted of germination paper rolls with soybean seeds, to evaluate first germination count tests, accelerated aging, cold test, root and shoot length, electrical conductivity, dry root mass and aerial part and total germination. The treatments with biostimulant in the seed under Glyphosate underdoses increase the total germination of the seedlings and present greater vigor for the resistance tests, however it reduces the vigor and reduces the growth rate and dry matter accumulation of the aerial part and root.